(untitled) (Research, Society and Development, 2020)
Objective: to report the experience of nursing residents in the context of the pandemic COVID-19 in a university outpatient care unit in the State of Rio de Janeiro. Method: This is an experience report about the work of nursing residents in the context of the referred pandemic, under the supervision of teachers, tutors and preceptors of the Faculty of Nursing at the State University of Rio de Janeiro. Results: Regarding the activities developed by residents on an outpatient basis during the pandemic, the implementation of the care flows stands out; the nursing consultation of users, including symptomatic health professionals; participation in training on the use of personal protective equipment and other work process management activities. Conclusion: the reported experience allowed the articulation and integration between teaching-service through assistance activities in the context of the pandemic, on an outpatient basis and enabled resident nurses to experience a unique experience in the global context of COVID-19.